Electronic support tools for identification and management of rice weeds in Africa for better-informed agricultural change agents - Rodenburg, J.; Le Bourgeois, T.; Grard, P.; Carara, A.; Irakiza, R.; Makokha, D.W.; Kabanyoro, Ruth; Dzomeku, I.; Chiconela, T.; Malombe, I.; Sarra, S.; Ekeleme, F.; et al. (EDP Sciences, 2016)
We developed an interactive electronic weed identification tool, AFROweeds, and an online network, Weedsbook, for agricultural change agents to aid communication and offer assistance to rice farmers with specific weed problems. We collected quantitative and qualitative data to assess effectiveness and usefulness of these products with potential users. With the online version of AFROweeds, used on an electronic tablet, average weed identification time in the field was 7 min 6 s with 44% successful identifications. Poor mobile network coverage and slow internet were the main reasons for the relative long identification time and low success rate. A second trial was done with the offline version, pre-installed on a tablet. The average identification time was 6 min 34 s, with a success rate of 75%. The online network Weedsbook, established alongside AFROweeds, was assessed by the test users as a useful additional aid, enabling agricultural change agents and agronomists to exchange information or request assistance on all aspects of weeds and weed management. The potential improvements of both products are discussed.